High diagnostic yield of syndromic intellectual disability by targeted next-generation sequencing. Issue 2 (12th September 2016) - Martínez, Francisco; Caro-Llopis, Alfonso; Roselló, Mónica; Oltra, Silvestre; Mayo, Sonia; Monfort, Sandra; Orellana, Carmen
Abstract : Background: Intellectual disability is a very complex condition where more than 600 genes have been reported. Due to this extraordinary heterogeneity, a large proportion of patients remain without a specific diagnosis and genetic counselling. The need for new methodological strategies in order to detect a greater number of mutations in multiple genes is therefore crucial. Methods: In this work, we screened a large panel of 1256 genes (646 pathogenic, 610 candidate) by next-generation sequencing to determine the molecular aetiology of syndromic intellectual disability. A total of 92 patients, negative for previous genetic analyses, were studied together with their parents. Clinically relevant variants were validated by conventional sequencing. Results: A definitive diagnosis was achieved in 29 families by testing the 646 known pathogenic genes. Mutations were found in 25 different genes, where only the genes KMT2D, KMT2A and MED13L were found mutated in more than one patient. A preponderance of de novo mutations was noted even among the X linked conditions. Additionally, seven de novo probably pathogenic mutations were found in the candidate genes AGO1, JARID2, SIN3B, FBXO11, MAP3K7, HDAC2 and SMARCC2 . Altogether, this means a diagnostic yield of 39% of the cases (95% CI 30% to 49%). Conclusions: The developed panel proved to be efficient and suitable for the genetic diagnosis of syndromic intellectual disability in a clinical setting. Next-generation sequencing has the potential for high-throughput identification of genetic variations, although the challenges of an adequate clinical interpretation of these variants and the knowledge on further unknown genes causing intellectual disability remain to be solved.